2009
DOI: 10.2217/fmb.09.18
|View full text |Cite
|
Sign up to set email alerts
|

The Gingipains: Scissors and Glue of the Periodontal Pathogen, Porphyromonas Gingivalis

Abstract: The anaerobic bacterium, Porphyromonas gingivalis, is associated with chronic periodontal disease (periodontitis or gum disease). The disease is not only the leading cause of tooth loss in the developed world, but is associated with a number of systemic diseases, such as cardiovascular disease and diabetes. The most potent virulence factors of this bacterium are the gingipains, three cysteine proteases that bind and cleave a wide range of host proteins. This article summarizes current knowledge of the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 169 publications
0
77
0
2
Order By: Relevance
“…Notably, no change in expression of the recently described Sov/PorT gingipain secretion system (Ishiguro et al, 2009;Sato et al, 2010) was observed in our microarray dataset. The importance of the gingipains has been well studied, and they have been shown to have a role in pigmentation, fimbriation and haemin utilization (Fitzpatrick et al, 2009). While their involvement in cell invasion is well established, the exact mechanism by which they influence cell uptake is less clearcut.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, no change in expression of the recently described Sov/PorT gingipain secretion system (Ishiguro et al, 2009;Sato et al, 2010) was observed in our microarray dataset. The importance of the gingipains has been well studied, and they have been shown to have a role in pigmentation, fimbriation and haemin utilization (Fitzpatrick et al, 2009). While their involvement in cell invasion is well established, the exact mechanism by which they influence cell uptake is less clearcut.…”
Section: Discussionmentioning
confidence: 99%
“…The best-characterized virulence determinants of the oral pathogen P. gingivalis are the extracellular arginine-specific proteases RgpA and RgpB and the lysine-specific protease Kgp, which are collectively known as gingipains (Nakayama et al, 1996b;Fitzpatrick et al, 2009;Kadowaki et al, 2007). There is much evidence for the role of these proteases in P.…”
Section: Stability Of the Invasive Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…The Gram-negative anaerobic bacterium Porphyromonas gingivalis is a major periodontal pathogen (Bostanci & Belibasakis, 2012). Tissue damage caused by P. gingivalis is mainly induced by a cocktail of secreted specialized toxin proteins, the gingipains (Fitzpatrick et al, 2009). The active release of gingipains at the bacterial cell surface is catalyzed by a recently identified multiprotein complex called the type IX secretion system (T9SS; Sato et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to direct invasion, periodontal bacteria can release products and components into the circulation and induce pro-atherogenic responses in endothelial cells. It has been shown that outer membrane vesicles, 9 gingipains from Porphyromonas gingivalis, 10 and free soluble bacterial components from Aggregatibacter actinomycetemcomitans 11 irritate endothelial cells and induce inflammation. Leakage of pro-inflammatory cytokines (IL-1, IL-6, TNFa) and other chemokines from the ulcerated periodontium causes the production of acute-phase proteins (i.e.…”
mentioning
confidence: 99%